2020
DOI: 10.1038/s41467-020-19879-3
|View full text |Cite
|
Sign up to set email alerts
|

Trans- and cis-acting effects of Firre on epigenetic features of the inactive X chromosome

Abstract: Firre encodes a lncRNA involved in nuclear organization. Here, we show that Firre RNA expressed from the active X chromosome maintains histone H3K27me3 enrichment on the inactive X chromosome (Xi) in somatic cells. This trans-acting effect involves SUZ12, reflecting interactions between Firre RNA and components of the Polycomb repressive complexes. Without Firre RNA, H3K27me3 decreases on the Xi and the Xi-perinucleolar location is disrupted, possibly due to decreased CTCF binding on the Xi. We also observe wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 100 publications
0
31
0
Order By: Relevance
“…Their dynamic chromatin enrichment patterns might be associated with their roles in regulating gene expression during the cell fate transition. For example, chromatin associated lncRNA XIST in cis regulates X chromosome inactivity over long genomic distance; and chromatin associated lncRNA FIRRE has both trans - and cis -acting effects on epigenetic features [ 54 ]. In addition, the dissociation of lncRNAs from chromatin is also important for their regulatory roles, such as lncRNA A-ROD was shown to enhance its upstream gene DKK1 transcription at its release from chromatin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their dynamic chromatin enrichment patterns might be associated with their roles in regulating gene expression during the cell fate transition. For example, chromatin associated lncRNA XIST in cis regulates X chromosome inactivity over long genomic distance; and chromatin associated lncRNA FIRRE has both trans - and cis -acting effects on epigenetic features [ 54 ]. In addition, the dissociation of lncRNAs from chromatin is also important for their regulatory roles, such as lncRNA A-ROD was shown to enhance its upstream gene DKK1 transcription at its release from chromatin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Cis-regulation has been extensively studied in the regulatory function of lncRNAs on nearby genes to govern cell fate. [22][23][24] Therefore, we explored the nearest PCG, ARRDC3, which was 54 kilobytes away from LUCAT1. However, ARRDC3 expression had no change when LUCAT1 was knocked down or overexpressed (Figures S6E-S6H), which suggested that LU-CAT1 might not regulate the expression of apoptosis-related proteins through the cis-pathway.…”
Section: Lucat1 Regulates Foxq1 Expression In a Jmjd6-dependent Mannermentioning
confidence: 99%
“…FIRRE forms “RNA clouds” in the nucleus, binds the nuclear matrix protein HNRNPU (heterogeneous nuclear ribonucleoprotein U), and serves as a platform for trans-chromosomal associations [ 63 ]. FIRRE is transcribed from the active X chromosome and acts in trans and cis to maintain X chromosome inactivation [ 64 ]. No reports of FIRRE/LNC01200 in BC were located in PubMed.…”
Section: Resultsmentioning
confidence: 99%